Analisis Node Dengan Metode Degree Centrality Dan Follower Rank Pada Tagar Twitter - Erits Talapessy; Hendry Hendry (JURIKOM (Jurnal Riset Komputer), 2022)
Twitter is one of the most popular social media platform as a means of information and interaction with other people. Since its launch in 2006, Twitter has been classified as a microblogging site. Data in the form of node analysis (actors) on Twitter can be analyzed using a social network analysis method approach. This study was designed to analyze data on tweet containing the hastag “#LuhutPenghisapDarahRakyat”. This analysis uses the degree centrality method to identify influential nodes (actors) and the follower rank method to find popular nodes (actors). The data were 2803 nodes and 8030 edges data was taken from November 6,2021 to November 7,2021. The results show that the @arthan38836243 account is the actor with the higshest degree centrality value, which is 265 and the @teriwinarno account is the actor with the highest popularity value or follower rank, which is 0.988081224. This shows that influential actors are not necessarily the same as popular actor. This studt that among the 10 main actors with the highest degree centrality value, one of the actors was a buzzer account on Twitter